2021
DOI: 10.1136/bjophthalmol-2021-319067
|View full text |Cite
|
Sign up to set email alerts
|

Three-year results of phase I retinal gene therapy trial for CNGA3-mutated achromatopsia: results of a non randomised controlled trial

Abstract: AimsTo determine long-term safety and efficacy outcomes of a subretinal gene therapy for CNGA3-associated achromatopsia. We present data from an open-label, nonrandomised controlled trial (NCT02610582).MethodsDetails of the study design have been previously described. Briefly, nine patients were treated in three escalating dose groups with subretinal AAV8.CNGA3 gene therapy between November 2015 and October 2016. After the first year, patients were seen on a yearly basis. Safety assessment constituted the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Of these, the vast majority are caused by mutations in either CNGA3 or CNGB3 genes ( Kohl et al, 2004 ; Liang et al, 2015 ; Zelinger et al, 2015 ; Sun et al, 2020 ). Current clinical trials are testing gene-therapeutic interventions to treat congenital ACHM by restoring cone function in the eye ( Fischer et al, 2020 ; Reichel et al, 2021 ; NCT03758404, NCT03001310, NCT03278873, NCT02935517, NCT02599922, and NCT02610582).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the vast majority are caused by mutations in either CNGA3 or CNGB3 genes ( Kohl et al, 2004 ; Liang et al, 2015 ; Zelinger et al, 2015 ; Sun et al, 2020 ). Current clinical trials are testing gene-therapeutic interventions to treat congenital ACHM by restoring cone function in the eye ( Fischer et al, 2020 ; Reichel et al, 2021 ; NCT03758404, NCT03001310, NCT03278873, NCT02935517, NCT02599922, and NCT02610582).…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence that cortical plasticity is still possible later in life was provided by an fMRI study reporting increased responses in visual cortex following gene therapy when participants with Leber’s Congenital Amaurosis were treated in adulthood ( Mowad et al, 2020 ). In ACHM, early studies also report promising but variable results following gene therapy ( Farahbakhsh et al, 2020 ; Fischer et al, 2020 ; Reichel et al, 2021 ). In a study of two adult ACHM participants, minor improvements in visual acuity and a reduction in levels of photoaversion were found following treatment ( McKyton et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, current therapeutic approaches successfully restored cone function in animal models [ 40 , 41 ]. However, first phases I/II clinical gene therapy trials in human ACHM only showed a very limited effect on the cone function restoration [ 42 , 43 ]. In human trials, changes in ffERG responses could not be observed, although all previously published ACHM animal models showed a clear improvement in ffERG responses upon gene augmentation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that gene therapy can effectively restore cone function in CNGA3-deficient mouse models [ 17 , 18 ]. Recently, phase I/II retinal gene therapy trials for CNGA3 -mediated achromatopsia demonstrated some level of cone photoreceptor function restoration in adult patients [ 19 , 20 ]. These experiments are timely in light of four ongoing adeno-associated virus (AAV) gene supplementation trials in adult cone dystrophy patients; in one of these trials, early electroretinogram (ERG) efficacy data suggested that cone function was not improved by AAV:: CNGA3 gene augmentation [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, phase I/II retinal gene therapy trials for CNGA3 -mediated achromatopsia demonstrated some level of cone photoreceptor function restoration in adult patients [ 19 , 20 ]. These experiments are timely in light of four ongoing adeno-associated virus (AAV) gene supplementation trials in adult cone dystrophy patients; in one of these trials, early electroretinogram (ERG) efficacy data suggested that cone function was not improved by AAV:: CNGA3 gene augmentation [ 19 , 20 , 21 ]. However, it is still unknown whether treating younger patients will result in greater functional gains by treating patients in a timely manner during the optimal therapeutic window for amblyopia, a visual impairment caused by the inability of the eyes and brain to work together with no causative structural abnormalities in the eyes or visual pathways.…”
Section: Introductionmentioning
confidence: 99%